2013
DOI: 10.1093/toxsci/kft211
|View full text |Cite
|
Sign up to set email alerts
|

Oral Propylparaben Administration to Juvenile Male Wistar Rats Did Not Induce Toxicity in Reproductive Organs

Abstract: Parabens are in widespread use as preservatives in drugs. In the late 1990 s, concerns were raised about their capacity to disrupt endocrine function based on in vitro data and in vivo uterotrophic tests. Studies in juvenile male rats provided conflicting results on pospubertal sperm production. In an exploratory pharmacokinetic study, Wistar male rats received a single dose of propylparaben (PP) at 3, 10, 100, or 1000 mg/kg, orally on postnatal day (PND) 31. Plasma PP concentrations were quantifiable up 8h af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 35 publications
0
37
1
Order By: Relevance
“…Aubert et al (2012) (Aubert et al, 2012) reflecting poor absorption through the 77 dermal route. Gazin et al (2013) found no measureable levels of PP 78 in plasma of rats 4 h post a single oral bolus up to 1000 mg/kg and 79 kinetics were non-linear at doses above 10 mg/kg. The only controlled dosing study in humans was a 5 day dermal 178 exposure study reported Q6 by Janjua et al (2008).…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Aubert et al (2012) (Aubert et al, 2012) reflecting poor absorption through the 77 dermal route. Gazin et al (2013) found no measureable levels of PP 78 in plasma of rats 4 h post a single oral bolus up to 1000 mg/kg and 79 kinetics were non-linear at doses above 10 mg/kg. The only controlled dosing study in humans was a 5 day dermal 178 exposure study reported Q6 by Janjua et al (2008).…”
mentioning
confidence: 83%
“…In vitro studies of metabo-58 lism in microsomal systems from various tissues including liver, 59 intestine and skin also reported that parabens are rapidly 60 hydrolyzed to 4-hydroxybenzoic acid (pHBA) in mammals (Abbas 61 et al, 2010;Jewell et al, 2007a,b;Ozaki et al, 2013) by 62 carboxylesterases. Parabens are also directly conjugated with 63 glucuronide, sulfate or glycine prior to excretion (Abbas et al,64 2010; Gazin et al, 2013;Ye et al, 2006Ye et al, , 2009. There are notable 65 differences in the predominant conjugate seen between rats and 66 humans.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Parabens are rapidly hydrolysed in vivo by carboxylesterases (mainly in skin, plasma and liver) to PHBA, a common metabolite for all parabens, which is nontoxic, ubiquitous in human nutrition and possesses no or negligible oestrogenic activity. 18 Concerns over potential carcinogenic activity of parabens have been consistently ruled out in the various expert reviews cited above. Kinetic investigations on several parabens have been undertaken in rats, 16,19 and the results are summarized in the most recent SCCS review, as follows:…”
Section: Propylparabenmentioning
confidence: 99%
“…In their most recent review in 2013, 17 SCCS evaluated Gazin et al's 8-week oral toxicity study (PND 21-77) on PP 18 with its associated TK data. PP was rapidly absorbed; for total PP (free and conjugated), the maximum plasma concentrations were generally observed 0.25-0.5 h after dosing.…”
Section: Pp As a Cosmetics Ingredientmentioning
confidence: 99%